2019
DOI: 10.1002/kjm2.12062
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of iron status and interplay between lipid peroxidation and antioxidant capacity in common hemoglobin variants in Osun State, southwestern Nigeria

Abstract: INTRODUCTION Hemoglobin (Hb) and iron are prooxidants in nature and sources of free radicals in the biological system of all Hb phenotypes. Recent evidence linked abnormal hemoglobin S and C (HbSC) in sickle cell disease (SCD) to various complications in multiple oxidative processes. However, similar studies in relation to abnormal Hb traits are sparse. Besides, reports on activities of antioxidant enzymes and iron status in SCDs are still contradictory. This study assessed the interplay between lipid peroxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…A study performed in HbSC and HbSS children showed lower plasma advanced oxidation protein product (AOPP) concentrations in the former group compared to the later, but no difference in malondialdehyde (MDA) levels was observed. 18 This finding is in agreement with the study of Antwi-Boasiako et al 19 but contrasts with the results of Ajibola et al 20 who showed lower MDA levels in HbSC patients. Torres et al 21 compared the plasma concentrations of several cytokines between HbSC and HbSS patients without HU therapy and showed similar levels of IL-1β but lower levels of IL-8 in HbSC.…”
Section: Introductionsupporting
confidence: 80%
“…A study performed in HbSC and HbSS children showed lower plasma advanced oxidation protein product (AOPP) concentrations in the former group compared to the later, but no difference in malondialdehyde (MDA) levels was observed. 18 This finding is in agreement with the study of Antwi-Boasiako et al 19 but contrasts with the results of Ajibola et al 20 who showed lower MDA levels in HbSC patients. Torres et al 21 compared the plasma concentrations of several cytokines between HbSC and HbSS patients without HU therapy and showed similar levels of IL-1β but lower levels of IL-8 in HbSC.…”
Section: Introductionsupporting
confidence: 80%
“…Elevated levels of lipid peroxides and their metabolites, such as 4-HNEs and MDAs are consistently found across various tissues, particularly during IRI and iron overload situations ( Hebbel et al, 2020 ). These accumulations are marked by increased protein oxidation, oxidant species, and lipid peroxidation products, especially in the kidney, liver, brain and lungs, indicating ferroptosis’s significant role in SCD tissue damage ( Kaul and Hebbel, 2000 , Ajibola et al, 2019 , Park et al, 2019 , Antwi-Boasiako et al, 2020 , Hebbel et al, 2020 , Engwa et al, 2021 ).…”
Section: Ferroptosis – Vaso-occlusion and Hemolysis In Scdmentioning
confidence: 99%
“…The oxidative stress level is determined by the body's ability to detoxify the produced ROS. Fatigue, memory loss, muscle and joint pain, decreased vision, headaches, and nose sensitivity are ranked as moderate oxidative stress symptoms [8]. Cancer, respiratory disease, Parkinson's disease, heart disease, arthritis, stroke, immune deficiency, emphysema, and many ischemic or inflammatory conditions are symptoms of higher levels of free radical production [9].…”
Section: Introductionmentioning
confidence: 99%